Characterization of Pseudomonas aeruginosa phage K5 genome and identification of its receptor related genes. (16th September 2016) - Li, Lingyan; Pan, Xuewei; Cui, Xiaoli; Sun, Qinghui; Yang, Xiaojing; Yang, Hongjiang
Abstract : Phage genomic information and the nature of host‐phage interactions are important for phage applications. In this study, Pseudomonas aeruginosa phage K5 is characterized as a linear double‐stranded genomic DNA molecule of 93, 754 bp with identical 1182‐bp direct terminal repeats. Comparative genomic analysis reveals that phage K5 is highly homologous to the "PaP1‐like" phages. Thirteen mutants resistant to phage K5 are screened in a transposon mutant library. The disrupted genetic loci are identified as gene Y880_RS05480 encoding a putative O‐antigen polymerase Wzy and gene wapH encoding a glycosyltransferase. The mutants are confirmed by the complementation experiment. The production of biofilm and the profile of lipopolysaccharide (LPS) are further analyzed in the Y880_RS05480 mutant. Our data indicate that LPS is the receptor of phage K5.